Fallopian tube patency diagnosed by laparoscopic chromopertubation in women with polycystic ovarian syndrome and non-subfertile controls: a retrospective case-control study - Daniel Mayrhofer; John Preston Parry; Marlene Hager; Rodrig Marculescu; Johannes Ott (IMR Press, 2022)
Background: Hyperandrogenism has been associated with tubal dysfunction. Previous studies have not used non-subfertile controls when assessing hyperandrogenic women through laparoscopic chromopertubation (LC), the gold standard for tubal patency testing. Methods: The objective of this retrospective study was to compare the results of LC between women with medication-resistant anovulatory polycystic ovary syndrome (PCOS, n = 202) and non-subfertile women with ovarian cysts (controls, n = 48). Results: There were no statistically significant differences between PCOS women and controls for the prevalence of bilateral tubal occlusion (2.5% versus 4.2%, respectively; p = 1.000) or overall rates for occlusion (7.4% of tubes assessed versus 6.3%, respectively; p = 0.828). More PCOS patients needed high pressure chromopertubation to demonstrate bilateral tubal patency than controls (12.4% versus 2.1%; p = 0.036). In the PCOS group, patients needing higher pressure to achieve patency demonstrated higher testosterone levels than women requiring typical pressure (0.66 ± 0.17 versus 0.47 ± 0.24 ng/mL; p = 0.001). Conclusions: For women with ovarian cysts and without subfertility, six percent of all Fallopian tubes are occluded. PCOS patients have similar rates of tubal occlusion, making these women a reasonable but more available control group for LC studies. Higher total testosterone levels were associated with higher LC pressures to demonstrate bilateral patency.